The power of words in educational environments (2019)
This paper presents a refl ection on the importance of language in educational scope, in particular about the power of words in the classroom. To develop this refl ection, we propose diff erent questions guiding this written text, including those ones concerning the importance of language, how to dialogue in educational contexts, which model students are setting up teachers’ words, and what kind of instructions and questions characterize educational environments. Hence, an analysis of the dynamics which are usually established in the classroom, the types of interaction that are conducive within, how they move on and who has the word in educational scenarios, is held. Finally, this article invites all diff erent levels of schooling teachers to open and keep up a space for refl ection on their own pedagogical practices, as an essential exercise for progressing in the construction of educational programs that encourage students to be more active, analytical, and foster them to have a word as well as recognizing others; taking the initiative and building knowledge through interactions including their cultural background embodying the texts.